The Effect of Religiosity Values on the Quality of Human Resources: A Case Study on DTA Nurul Huda Kecamatan Cinambo - Amaliah, Ima; Septiani Aisy, Shaffa; Nurheryanti, Vika; Allyanisa Hidayat, Safina; Fauzan Al Rifah, Cecep (KnE Social Sciences, 2023)
This study aims to identify the influence of religiosity values on the achievements of DTA Students of Nurul Huda Mosque, Cinambo District, Bandung City. To answer the research problem, a field survey was carried out by distributing questionnaires and interviews to the students of the Nurul Huda Mosque DTA. The population in this study was 120 people, but the sample studied was 65 respondents with the random sampling method. Measurement of religiosity and achievement were done using a Likert scale of 5 and testing of questionnaire instruments by conducting validity and reliability tests. The value of religiosity is developed in 5 dimensions, while achievement is developed in 2 dimensions, namely academic and nonacademic achievement. The estimation results partially concluded that of the five dimensions of religiosity, only one significant dimension, namely the intellectual property dimension was competitively religious. However, together the five dimensions of religiosity statistically affect the achievements of students of the Nurul Huda Mosque DTA. Therefore, it is necessary to strengthen the value of religiosity in prior to form a religious competitive character. Keywords: religiosity, achievement, human resources